A Phenomenology of/with Total Movement: Response to Erin Manning. (September 2014) - McNeilly, Jodie
In 'Wondering the world directly', Erin Manning criticizes phenomenology by drawing upon Merleau-Ponty's reflections on the problems of his own project and the criticisms of José Gil. Manning claims that phenomenology goes 'wrong' in its privileging of the subject and processes of intentionality: the 'consciousness–object distinction'. While phenomenology on this understanding alone is inadequate to account for movement and the body, process philosophy has the 'ability to create a field for experience that does not begin and end with a human subject'. This article responds to Manning's criticism by arguing that phenomenology never intended to perpetuate a concept of subject that fixes an inexorable gap between itself and objects. A historical assessment of subjectivity and intentionality in the work of five different authors, alongside critical points that address Manning's misconstrual of phenomenology, leads to an understanding of movement that need not 'outrun the subject' or become a precarious limit to perceptual experience because of its primacy.